(untitled) (Quinto Sol, 2018)
This work constitutes a first approach to the funerals of “fallen” soldiers, non-commissioned officers and officers in the so-called “struggle against subversion” between 1973 and 1976 and, more generally, it explores how in these rituals the figure of those who had “sacrificed” their lives was constructed. We start from the assumption that the production process of these deaths was made through the task of strong “psychological action” within the military ranks and that it was based on the paradigmatic figure of the soldier, non-commissioned and officer “fallen” by the “subversion”. We will focus on the analysis of the speeches, practices and rituals that different actors (relatives, authorities of the Armed Forces, “comrades of arms” or promotion, political leaders, religious) deployed within the framework of these events. It seems to us that such study is fundamental in explaining how a social climate of risks, dangers, but also of hatred, vengeance, and sacrifice was built, which can be a key to understanding the corporate commitment of the Armed Forces in the execution of repressive measures, which was institutionalized after the coup d’état of March 24th, 1976.